The Implementation of Gallery Walk for Teaching Mahārat al-Istimā’ - Syahiratunnisa, Sabilaa; Sauri, Sofyan; Fuadi, Farhan; Nugroho, Ihsan Iwan (Jurnal Pendidikan Islam, 2025)
Ineffective strategies for teaching listening skills (mahārat al-istimā’) at Pondok Pesantren Tahfidz Qolbul Qur’an Putri make the learning environment passive and boring. However, a gallery walk based on the Communicative Language Teaching (CLT) approach can be an innovative strategy for teaching mahārat al-istimā’. This study aims to describe the implementation of the gallery walk for teaching mahārat al-istimā’, reveal students’ responses to the gallery walk, and the impacts of the gallery walk on students’ mahārat al-istimā’. This study employed a qualitative-descriptive approach. Data collection in this study includes observation, interviews, and documentation techniques. The results of this study show that gallery walks successfully provide positive impacts and responses in mahārat al-istimā’ teaching by creating an active, collaborative, and enjoyable learning atmosphere with a student-centered concept. Students become more focused, enthusiastic, and motivated in listening. The students also show positive responses through their social interactions and understanding of the material. Thus, the gallery walk based on the CLT approach can be an innovative and effective strategy in improving the quality of teaching mahārat al-istimā’ in Islamic schools.